The Transcription Factor Foxc1 Promotes Osteogenesis by Directly Regulating Runx2 in Response of Intermittent Parathyroid Hormone (1–34) Treatment - Ouyang, Ningjuan; Li, Hongliang; Wang, Minjiao; Shen, Hongzhou; Si, Jiawen; Shen, Guofang (Frontiers in Pharmacology, 2020)
Parathyroid hormone (PTH) is a critical regulator of bone remodeling. Intermittent administration of PTH (1-34) stimulates osteogenesis and promote bone formation, however, the possible targets and underlying mechanisms have not been fully elucidated yet. In this study, functional links between PTH and Foxc1, a transcription factor reported to play a predominant role in regulating bone development and formation, were indicated. We determined the effect of Foxc1 on osteogenic differentiation in vitro and bone regeneration in vivo under the induction of intermittent PTH, and further explored its possible targets. We found that the expression level of Foxc1 was upregulated during osteogenic induction by intermittent PTH treatment and the elevated expression of Foxc1 induced by intermittent PTH treatment was inhibited by PTH1R silencing, while rescued by PTH supplement. By Foxc1 gain- and loss- of-function experiments in MC3T3-E1 cells, we demonstrated that Foxc1 could promote osteogenic differentiation induced by intermittent PTH treatment in vitro. Moreover, immunofluorescence analysis indicated the nuclear co-localization of Foxc1 with Runx2, while luciferase-reporter and chromatin immunoprecipitation analysis further confirmed that Foxc1 could directly bind to the P1 promoter region of Runx2, which plays an essential role in osteogenic differentiation and bone mineralization. Meanwhile, we also revealed that Foxc1 could promote bone regeneration induced by intermittent PTH treatment in vivo. Taken together, this study revealed the role and mechanism of Foxc1 in osteogenic differentiation in vitro and bone regeneration in vivo in response of intermittent PTH treatment.